Leggett fulfils dance pledge - New Straits Times, (2012)
MISS Universe Malaysia Kimberley Leggett dance with the WWF-Malaysia panda mascot at the official Earth Hour venue sponsor Sunway Pyramid on Earth Day on Sunday.